Application of Response Surface Methodology for Optimization of Cellulose Solution by Zinc Chloride - Zeng, G.M.; Wang, Y.L.; Qing, X.X.; Zhang, M.L.; Xing, J.; Ma, Y.F.; Xu, H.J. (Asian Journal of Chemistry, 2012)
Corn stover is a largely feasible and cheap renewable resource with low commercial value. An attractive alternative is utilization of corn stover for chemical industry, medicine, biochemistry etc. However, the production costs are still too high to apply on commercialization. The objective of this study was to use the response surface methodology (RSM) to optimization of cellulose salvation by zinc chloride after the steam explosion and characterization and map changes during zinc chloride pretreatments of corn stover. The solution of cellulose had been pretreated with 87 % zinc chloride at 139 ºC for 49 min resulted in an optimum solubility of 76.2 %. Zinc chloride pretreatment apparently damaged the surface of cellulose and significantly decreased the crystalline region, as evidenced by SEM and XRD analysis data. FTIR analysis indicated that zinc chloride pretreatment could breakage the hydrogen bond of crystalline region of the cellulose. The zinc chloride after steam explosion technique, as a novel pretreatment method, decreased crystalline region of cellulose by changing structural features.